Dynamic evolution control based power sharing method for hybrid energy storage system - Manandhar, Ujjal (2021)
In this study, a new dynamic evolution control (DEC) based power sharing method is proposed for hybrid energy storage system (HESS) with photovoltaic in the isolated DC grid application. The proposed control approach solves the current controller conflict problem in HESS and provides faster DC link voltage restoration. A DEC method is implemented to control the battery current, supercapacitor current and DC link voltage. A DEC method uses a predictive term and feed-forward term to regulate the current and voltage in the system. In the proposed control method, the battery supports the average power demand in the system. The supercapacitor supports the transient power demand, uncompensated power from the battery and error voltage term. Thus, it results in faster DC link voltage restoration and less stress in the battery system. The detailed design of the system parameters and controller parameters is presented in this study. Simulation and experimental studies validate the effectiveness of the proposed control method.